PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP KETERAMPILAN MEMBACA KELAS 2 DI SD NEGERI 76 TAROWANG: Pendidikan - Hasriani, Hasriani; Wafiq Azizah; Arvina, Arvina; Nurfadillah, Nurfadillah; Putri Cahaya; Mutmainnah, Mutmainnah; Haris, Haris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Make a Match learning model assisted by Wordwall digital media and learning videos on the reading skills of second-grade students at SD country 76 Tarowang. The research used a quantitative approach with a pre-experimental type and a One Group Pretest-Posttest Design, involving one class with 27 students. Data was collected thru reading comprehension tests administered before and after the implementation of the learning model. Data analysis was conducted with the assistance of the SPSS program using the Paired Sample T-Test. The research results indicate that the average reading skill score of students increased from 66.40 in the pretest to 85.20 in the posttest, with a significance value (Sig. 2-tailed) of 0.000 < 0.05, which means there is a significant difference between reading abilities before and after the treatment. Thus, the implementation of the Make a Match learning model assisted by Wordwall and learning videos significantly affects the improvement of students' reading skills. This model has proven capable of creating a fun, interactive learning environment that encourages student participation in the Indonesian language learning process in elementary school.